Choosing the right incentive strategy for research and development in neglected diseases - Maurer Stephen M (The World Health Organization, 2006)
For the first time in history, worldwide neglected disease budgets may be large enough to deliver a new drug every few years. That said, sponsors will only succeed if they extract maximum value from every dollar spent. This paper reviews possible cost-containment strategies and provides an evidence-based framework for choosing between them. Current proposals can be categorized as "end-to-end" proposals which require the sponsor to set a single reward for companies that complete the entire drug discovery process or "pay-as-you-go" schemes in which sponsors offer repeated rewards as drug candidates progress through the pipeline. A generic weakness of end-to-end proposals is that rewards are likely to be 20-30% higher than they would be in an equivalent pay-as-you-go programme. However, the benefits of pay-as-you-go programmes may be lost if commercial pharmaceutical companies are substantially better at choosing successful programmes than are their non-profit counterparts. The efficiency of pay-as-you-go methods depends on sponsors" willingness to withdraw funding from failed drug discovery programmes.